1998
DOI: 10.1021/ic971342h
|View full text |Cite
|
Sign up to set email alerts
|

Bond Valence Sums in Coordination Chemistry Using Oxidation-State-IndependentR0Values. A Simple Method for Calculating the Oxidation State of Iron in Fe−O Complexes

Abstract: The use of the bond valence sum in Fe−O complexes is discussed using data from the Cambridge Structural Database. The oxidation state of Fe in complexes containing Fe bonded only to O can be calculated by ∑ i exp[(R 0 − r i )/b], where r i is the observed Fe−O i bond length, R 0 is a constant = 1.745 Å, and b is taken to be 0.37. The R 0 value can be viewed as a bond length of unit valence. Deviations from an integer value indicate a problem with the crystal structure or electron delocalization in multinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…Compared with the work of Brese & O'Keeffe (1991), we find a systematic difference of ca 0.077 Å between bond-valence parameters determined from organic and inorganic structures. The same tendencies can also be observed for the bond-valence parameters calculated for lanthanide-oxygen bonds (Trzesowska et al, 2004) and other metal-oxygen bonds (Wood & Palenik, 1998;Wood et al, 2000;Kanowitz & Palenik, 1998).…”
Section: Resultssupporting
confidence: 71%
“…Compared with the work of Brese & O'Keeffe (1991), we find a systematic difference of ca 0.077 Å between bond-valence parameters determined from organic and inorganic structures. The same tendencies can also be observed for the bond-valence parameters calculated for lanthanide-oxygen bonds (Trzesowska et al, 2004) and other metal-oxygen bonds (Wood & Palenik, 1998;Wood et al, 2000;Kanowitz & Palenik, 1998).…”
Section: Resultssupporting
confidence: 71%
“…Table 1 summarizes the optimized R 0 parameters for iron(II) and iron(III), estimated using both homoleptic and heteroleptic metal-binding sites within the first coordination sphere, and compares them with several previous studies (Brese & O’Keeffe, 1991; Liu & Thorp, 1993; Kanowitz & Palenik, 1998). While most of the R 0 parameters derived here for iron agree within ±0.1 Å with previously reported values, we found that the Fe—N R 0 parameters reported previously appear to agree well only with the corresponding high-spin (HS) species.…”
Section: Resultsmentioning
confidence: 98%
“…The oxidation-state assignment process outlined in x2.3 allows us to divide our input structures into ferrous and ferric subsets upfront and model the two populations independently. This initial assignment results in a major peak Table 1 Optimized R 0 parameters (in Å ) derived for iron(II) and iron(III), compared with reference literature values (Brese & O'Keeffe, 1991;Liu & Thorp, 1993;Kanowitz & Palenik, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Chlorinebearing K -rich amphiboles have been reported from various rock types (cf., Deer et al, 1997). A crystal -chemical Allmann (1975), Brown and Altermatt (1985), Brese and O'Keeffe (1991) and Kanowitz and Palenik (1998). Table 6.…”
Section: Disucussionmentioning
confidence: 99%